Community hydric monitoring: homegrown knowledge as local and environmental defense in Argentina, Peru and Colombia - Astrid Ulloa; Julieta Godfrid; Gerardo Damonte; Catalina Quiroga; Ana Paula López (Íconos)
The expansion of large- scale mining projects in Latin America has led to the application of several different institutional and business-endorsed water monitoring systems. These have attempted to deal with their vast environmental consequences. The methods are based on the devaluation of other forms of knowledge. As a response to this tendency, community hydric monitoring (MHC in Spanish) has been proposed in order to empower community-based knowledge. Alternative forms of knowledge are seen as useful ways of illuminating the impact of mining on water supplies. Likewise, communities have been active in developing connections with Academia, NGO´s and social organizations to promote a meaningful dialogue with conventional technical paradigms. These exchanges aim to generate counter-narratives about water quality, as well as to develop a defense strategy against mining. Here we focus on the research done between 2018 and 2020 in Argentina (Veladero), Peru (Antapaccay- Expansión Tintaya) and Colombia (Cerrejón). In all these cases, the local population has developed its own MHC, based on local knowledge about water. We analyze the information asymmetries resulting from socio-environmental inequality and we advocate for a wider discussion which incorporates community-generated knowledge, and more diverse and comprehensive approaches to understanding, knowing and relating to water and to local conditions.